Perceptions about health-risk awareness and lifestyle change among women at risk for developing cardiometabolic disease: a qualitative study - Jacqueline Kent-Marvick; Stephanie Lynn St. Clair; Alycia A. Bristol; Bryan Gibson; Sara E. Simonsen (Springer, 2024)
Abstract Background The reproductive years provide a window into future risk for Type 2 Diabetes (T2DM); women's risk is seven to 10 times higher after gestational diabetes (GDM) and two to four times higher after a hypertensive disorder of pregnancy (HDP). Targeting reproductive-aged women at high risk for T2DM could reduce future incidence. However, little is known about such women's diabetes risk perceptions, barriers to/motivators of lifestyle change or their knowledge about lifestyle change-information essential to understanding how to engage these at-risk women in tailored prevention programs promoting long-term health. This study's aims were to describe: among reproductive-aged women at high risk for T2DM, what is/are (1) personal health-risk awareness, (2) lifestyle-change interest, and (3) barriers to/motivators of participation in lifestyle-change programs? Methods Women aged 18 and older were eligible if they had one of the following health risks: (1) GDM or HDP during pregnancy, (2) prediabetes diagnosis, or (3) BMI classified as obese. Three Zoom focus groups, organized by risk group, were conducted with a total of 20 participants. Qualitative content and thematic analysis were used for the focus-group transcriptions. Results Women's personal health-risk awareness was limited and generalized (e.g., being overweight might lead to other risks) and rarely reflected awareness connected to their personal health history (e.g., GDM increases their lifetime risk of T2DM). Participants had at least one of the outlined eligibility health risks (e.g., GDM, prediabetes); they did not believe their healthcare providers sufficiently followed or addressed those risks. All women expressed interest in making healthy-lifestyle changes, including engagement in formal programs, but they identified multiple barriers to healthy-behavior change related to being "busy moms." Women emphasized the need for social support and realistic solutions that accounted for the dynamics of motherhood and family life. Common motivators included the desire to maintain health for their families and to set a good example for their children. Conclusions Participants lacked knowledge and were eager for information. Healthcare improvement opportunities include better coordination of care between primary and specialty-care providers, and more frequent communication and education on diabetes-related health risks and long-term health. Formal lifestyle programs should tailor content by providing multiple formats and flexibility of scheduling while leveraging peer support for sustained engagement.